Psychosocial Assessment of Patients Attending Geriatrics OPD at Civil Hospital in Ahmedabad - Mathur, Neeta (National Journal of Community Medicine, 2018)
Background: Health status is an important factor that has a sig- nificant impact on the quality of life of an elderly population. The aim of the study is to determine the medical, psychological and social characteristics among geriatric patients. Methods: A hospital based study was conducted in Civil Hospital, Ahmedabad. The patients aged 65 years and above were included in the geriatrics outpatient department. The geriatric patients were interviewed during their geriatric clinic visit using a structured questionnaire regarding their socio-demographic characteristics, addiction history, perceived health status and a short version of the geriatric depression scale. Results: Depression was found in 31.5% of the patients. It was due to combined effect of sedentary life style, medication used and greater number of reported symptoms. Not due to difference in gender, age group, loss of spouse, employment, educational status & living arrangement. Conclusions: In order to improve the health status of the geriatric patients it is important to carry out more studies in different areas to identify various factors that are related to psychological distress and disability, which should lead to efforts to develop effective programmes in disease prevention.